PENGARUH TEKNIK KOMUNIKASI MENGGUNAKAN BONEKA TANGAN TERHADAP PERUBAHAN TINGKAT KECEMASAN AKIBAT HOSPITALISASI PADA ANAK PRASEKOLAH DI RUANG EDELWEIS RSUD M. YUNUS BENGKULU - Rafidaini Sazarni Ratiyun (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
ABSTRACT Hospitalization is the cause of anxiety in children undergoing hospital care. The number of stressors experienced by children when undergoing hospitalization has a negative impact that interferes with children's development. The hospital environment can be a cause of stress and anxiety in children. The purpose of this research is to determine the effect of communication techniques using hand puppets to changes in levels of anxiety due to hospitalization in preschool children in the Edelweis room M. Yunus Hospital Bengkulu. The research design used was pre-experimental using a one-group pretest-posttest design and using a purposive sampling technique, with a total sample of 30 respondents. The study population was preschool children who were treated in the Edelweis room of M. Yunus Hospital Bengkulu in April to May 2019. Data collection uses the Spence Children Anxiety Scale questionnaire (parent report) before and after the communication technique using hand puppets. Wilcoxon Signed Rank Test obtained Z value of -4.791 with an Asymp value. Sig (p) = 0,000, because the value of p <0.05, thus it can be concluded that there is an influence of communication techniques using hand puppets to change levels of anxiety due to hospitalization in preschool children in the Edelweis room of M. Yunus Hospital Bengkulu. Health workers, especially nurses, can apply communication techniques using hand puppets to reduce anxiety in preschoolers when hospitalized. Keyword: Hand Puppets, Anxiety, Hospitalization, Communication Techniques